Money and power in Hellenistic Bactria - Glenn, Simon. (New York)
xv, 394 sayfa, [1] sayfa harita
Keywords: “The coins produced by the kings of the Graeco-Bactrian kingdom of the third and second centuries BC are the best and, in some cases only, primary source of evidence for the history of the period. The lack of context has, however, often led to highly speculative uses of the numismatic evidence in previous historical reconstructions. Money and Power in Hellenistic Bactria returns the focus to the coins themselves and presents the results of a full die study of the issues of Euthydemus I, Demetrius I, Euthydemus II, Pantaleon, Agathocles, and Antimachus I. In doing so it proposes a new, soundly based history of the Graeco-Bactrian kingdom under these kings based on a thorough understanding and suggested reconstruction of these enigmatic coins.” --